The effect of hydrochloric acid on microstructure of porcine (Sus scrofa domesticus) cortical bone tissue - Sabolová, Veronika; Brinek, Adam; Sládek, Vladimír (Forensic science international, 2018)
We evaluated the degradation of cortical bone tissue by hydrochloric acid (HCl) since intentional bone decalcification in a forensic context has not been studied on a histomorphological level. We used 70 pig metatarsal bones split into subsamples and immersed in one of three concentrations of acidic solutions (0.5M, 1M, 2M HCl) for two and four hours. We analyzed the cortical thicknesses on transversal cross-sections, thicknesses of the three histomorphologically distinct zones present in acid-immersed bones, and number and area of crystals present in one of the zones. Furthermore, we analyzed the ratio of calcium to phosphorus (Ca:P). We observed a division of the cortical bone cross section into three distinctive zones: demineralized matrix (DM) in the periosteal part of bone, middle contact zone (CZ), and mineralized matrix (MM) in the endosteal part of bone. With increasing acid concentration and time of immersion (from 0.5M HCl for 2h to 2M HCl for 4h), the thickness of DM increased by 67%, the thickness of CZ increased by 56%, and the thickness of MM decreased by 32%. The Ca:P ratio in the contact zone of acid-treated samples did not change significantly with changing acid concentration and time of immersion. The Ca:P ratio of the CZ decreased by 10% when compared to the Ca:P ratio of MM in acid-treated samples. Moreover, we observed crystals on the outer periosteal border of the DM zone, in the CZ, and in the MM Haversian/Volkmann's canals. The size and number of the crystals in the CZ of acid-treated bones increased with acid concentration and time of acid immersion. Moreover, we also observed significant differences in all analyzed properties between anatomical regions. Due to varying reactions to acid immersion among anatomical regions, bone micro-degradation should be observed separately for each region.
Keywords: Calcium; Periosteum; Hydrochloric acid; kyselina chlorovodíková; Sus scrofa; Micro CT; fosfor; Metatarsal Bones; vápník; Microscopy, Electron, Scanning; spektrometrie rentgenová emisní; soudní patologie; zvířata; EDX; Hydrochloric Acid; Taphonomy; kortikální kost; rentgenová mikrotomografie; Phosphorus; Forensic Pathology; mikroskopie elektronová rastrovací; Cortical Bone; Spectrometry, X-Ray Emission; X-Ray Microtomography; metatarzální kosti; Animals; okostice; SEM